Redox regulation of the Calvin–Benson cycle: something old, something new - Michelet, Laure; Zaffagnini, Mirko; Morisse, Samuel; Sparla, Francesca; Pérez-Pérez, María Esther; Francia, Francesco; Danon, Antoine; Marchand, Christophe; Fermani, Simona; Trost, Paolo; Lemaire, Stéphane D. (Frontiers in Plant Science, 2013)
Reversible redox post-translational modifications such as oxido-reduction of disulfide bonds, S-nitrosylation and S-glutathionylation, play a prominent role in the regulation of cell metabolism and signaling in all organisms. These modifications are mainly controlled by members of the thioredoxin and glutaredoxin families. Early studies in photosynthetic organisms have identified the Calvin-Benson cycle, the photosynthetic pathway responsible for carbon assimilation, as a redox regulated process. Indeed, 4 out of 11 enzymes of the cycle were shown to have a low activity in the dark and to be activated in the light through thioredoxin-dependent reduction of regulatory disulfide bonds. The underlying molecular mechanisms were extensively studied at the biochemical and structural level. Unexpectedly, recent biochemical and proteomic studies have suggested that all enzymes of the cycle and several associated regulatory proteins may undergo redox regulation through multiple redox post-translational modifications including glutathionylation and nitrosylation. The aim of this review is to detail the well-established mechanisms of redox regulation of Calvin-Benson cycle enzymes as well as the most recent reports indicating that this pathway is tightly controlled by multiple interconnected redox post-translational modifications. This redox control is likely allowing fine tuning of the Calvin-Benson cycle required for adaptation to varying environmental conditions, especially during responses to biotic and abiotic stresses.